2012
DOI: 10.1073/pnas.1206672109
|View full text |Cite
|
Sign up to set email alerts
|

Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) induces cancer cell senescence by interacting with telomerase RNA component

Abstract: Oxidative stress regulates telomere homeostasis and cellular aging by unclear mechanisms. Glyceraldehyde 3-phosphate dehydrogenase (GAPDH) is a key mediator of many oxidative stress responses, involving GAPDH nuclear translocation and induction of cell death. We report here that GAPDH interacts with the telomerase RNA component (TERC), inhibits telomerase activity, and induces telomere shortening and breast cancer cell senescence. The Rossmann fold containing NAD + binding region on GAPDH is responsible for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 45 publications
(69 reference statements)
3
57
0
2
Order By: Relevance
“…However, accumulating evidence reveals its diverse functions in various cellular processes (7)(8)(9)(10)(11)(12)(13)(14). In this report, we identified a novel acetylation site (K254) in GAPDH.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, accumulating evidence reveals its diverse functions in various cellular processes (7)(8)(9)(10)(11)(12)(13)(14). In this report, we identified a novel acetylation site (K254) in GAPDH.…”
Section: Discussionmentioning
confidence: 70%
“…In addition to its role in energy production, GAPDH has been implicated in many cellular processes including DNA repair (7), tRNA export (8), membrane fusion and transport (9), endocytosis and nuclear membrane assembly (10), and cell death (11,12). Recently elegant studies also found GAPDH is involved in immunity (13) and senescence (14). The diverse functions of GAPDH are mainly regulated by its oligomerization, posttranslational modification and sub-cellular localization.…”
Section: F)-fluoro-2-deoxy-d-glucose (18f-fdg)mentioning
confidence: 99%
“…As a result, the GAPDH binding site for RNA remains unknown. Conflicting studies suggested that RNA binding is mediated by either the NAD ϩ binding domain alone (13,30,64) or by the entire GAPDH protein (36). Others proposed that RNA binds to the tetramer groove (39).…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, GAPDH acts as a key mediator of many oxidative stress responses, involving GAPDH nuclear translocation and induction of cancer cell senescence (Hwang et al, 2009;Nicholls et al, 2012). Interestingly, GAPDH interacts with mammalian RNA binding protein p54nrb (54-kD nuclear RNA binding protein) in the cytosol in a manner dependent on the dose of H 2 O 2 to exert a potential role in transcription or replication (Hwang et al, 2009).…”
Section: Role Of Gapc-atg3 Interaction In Autophagymentioning
confidence: 99%